Preparation method of high-strength heat-conducting material for rear cover of mobile phone

By using graphene oxide and aminopolyimide-polycarbonate copolymer as reinforcement in polycarbonate materials, combining bisphenol A type nitrobenzoyl chloride monomer with polycarbonate diol for esterification polymerization, forming an aminopolyimide-polycarbonate copolymer and melt blending with graphene oxide, the problem of insufficient mechanical strength and thermal conductivity of polycarbonate materials in the prior art is solved, and high strength and high thermal conductivity of materials are achieved.

CN119875347APending Publication Date: 2025-04-25DONGGUAN ZHENYU MOULD PLASTIC CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510132295.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-06
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The prior art is difficult to provide a polycarbonate material with high mechanical strength and good thermal conductivity, which is suitable for mobile phone back covers.

Method used

By using graphene oxide and amino polyimide-polycarbonate copolymer as reinforcement, a high-strength thermal conductivity material was prepared by combining bisphenol A-type nitrobenzoyl chloride monomer with polycarbonate diol for esterification polymerization to form an amino polyimide-polycarbonate copolymer and melt blended with graphene oxide.

Benefits of technology

It significantly improves the mechanical strength and thermal conductivity of polycarbonate materials, enhances the tensile strength, bending strength and thermal conductivity of the material, and meets the high-performance needs of the mobile phone back cover.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005261981880000021
    Figure BDA0005261981880000021
  • Figure BDA0005261981880000031
    Figure BDA0005261981880000031
  • Figure BDA0005261981880000081
    Figure BDA0005261981880000081
Patent Text Reader

Abstract

The invention relates to the technical field of polycarbonate, and discloses a preparation method of a high-strength heat-conducting material for a rear cover of a mobile phone, which comprises the following steps: heating and stirring graphene oxide and an amino polyimide-polycarbonate copolymer, adding the mixture and polycarbonate into a twin-screw extruder, and carrying out melt extrusion and granulation to obtain the high-strength heat-conducting material for the rear cover of the mobile phone. In the heating and stirring process of the amino polyimide-polycarbonate copolymer, amino groups of the amino polyimide-polycarbonate copolymer can react with carboxyl groups and epoxy groups on the surface of graphene oxide, so that a copolymer molecular chain is modified to the surface of graphene, the compatibility between graphene and a polycarbonate matrix is improved, and the dispersity of graphene is improved; the graphene has a better reinforcing effect, under the synergistic effect of the graphene and the polyimide-polycarbonate copolymer, the tensile strength and other mechanical properties of the polycarbonate material are improved, and the heat conductivity coefficient and heat-conducting property of the material can be further improved by the uniformly dispersed graphene.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polycarbonate, in particular to a method for preparing a high-strength thermal conductive material for a mobile phone back cover. Background Art

[0002] Polycarbonate has good flame retardancy, oxidation resistance, heat resistance and other properties, and is widely used in the fields of mobile phone housing, food and drug packaging, mechanical equipment, etc. Filling and modifying polycarbonate with nanomaterials is an effective method to improve its mechanical properties. Graphene, as a high-performance carbon nanomaterial, has important applications in polymer materials such as polycarbonate, polyurethane, and epoxy resin. Surface modification of graphene is a research hotspot. Patent CN112094491B discloses a method for preparing a graphene / polycarbonate composite material, which uses caprolactone monomer to graft and modify hydroxy graphene, and wraps polycaprolactone on the surface of graphene to prevent the agglomeration of graphene, and provides compatibility between graphene and polycarbonate, thereby improving the tensile strength, bending strength and other mechanical properties of polycarbonate materials. Compared with the patent, the present invention uses graphene oxide and amino polyimide-polycarbonate copolymer as reinforcing agents to significantly improve the mechanical strength and thermal conductivity of polycarbonate materials. Summary of the invention

[0003] The technical problem solved by the invention is to provide a polycarbonate material with high mechanical strength and good thermal conductivity for a mobile phone back cover.

[0004] The technical solution of the present invention is: a method for preparing a high-strength thermal conductive material for a mobile phone back cover:

[0005] Step S1, add N,N-dimethylformamide, bisphenol A type nitrobenzoyl chloride monomer, polycarbonate diol, and triethylamine into a reaction container, heat to 40-55° C., stir and react for 18-24 hours, pour the solution into ethanol, filter, wash with water and ethanol in turn, and dry to obtain a nitropolyimide-polycarbonate copolymer.

[0006] Step S2, add concentrated hydrochloric acid and iron powder with a mass fraction of 36-38% to a reaction vessel equipped with a condenser reflux tube, heat to 65-70°C, add N,N-dimethylformamide solution containing nitropolyimide-polycarbonate copolymer after stirring, then heat to 100-110°C, react for 12-18h, add water, filter, wash the filter cake with water, sodium hydroxide solution, and water in turn, and dry to obtain aminopolyimide-polycarbonate copolymer. The reaction formula is:

[0007]

[0008] Step S3, adding N,N-dimethylformamide and 0.5-3 parts by weight of graphene oxide into a reaction container, adding 8-25 parts by weight of amino polyimide-polycarbonate copolymer after ultrasonic dispersion, heating to 100-120°C, stirring for 12-24 hours, removing N,N-dimethylformamide by reduced pressure distillation, and adding the mixture and 100 parts by weight of polycarbonate into a twin-screw extruder after drying, with the temperature of zones 1 to 4 being 260-275°C, the head temperature being 250-260°C, the screw speed being 400-500r / min, melt extruding and granulating to obtain a high-strength thermal conductive material for a mobile phone back cover.

[0009] Furthermore, in step S1, the masses of bisphenol A-type nitrobenzoyl chloride monomer and triethylamine are 88-94% and 20-24% of the mass of polycarbonate diol, respectively.

[0010] Furthermore, in step S2, the masses of concentrated hydrochloric acid and iron powder are 2000-3000% and 290-440% of the mass of the nitropolyimide-polycarbonate copolymer, respectively.

[0011] Furthermore, the preparation method of bisphenol A type nitrobenzoyl chloride monomer is as follows: add acetic anhydride, 70-80% of the mass of acetic anhydride pyridine, bisphenol A type diether dianhydride (CAS No. 38103-06-9), 70-77% of the mass of bisphenol A type diether dianhydride 3-amino-5-nitrobenzoic acid (CAS No. 618-84-8) into a reaction container equipped with a condenser reflux tube, heat to 115-125° C., react for 12-18 hours, filter and wash with water and ethanol in turn, add the product to thionyl chloride after drying, heat to 60-70° C., react for 3-4 hours, remove thionyl chloride by reduced pressure distillation, and dry to obtain bisphenol A type nitrobenzoyl chloride monomer.

[0012] The reaction formula is:

[0013]

[0014] The technical effect of the present invention is as follows: the present invention utilizes a novel bisphenol A type nitrobenzoyl chloride monomer and polycarbonate diol to carry out esterification polymerization reaction, and then reduces the nitro group to obtain a polyimide-polycarbonate copolymer containing an amino group, and then melt blends it with graphene oxide and polycarbonate to obtain a high-strength thermal conductive material for a mobile phone back cover. The amino polyimide-polycarbonate copolymer bisphenol A structural unit and polycarbonate molecular chain have good compatibility with the bisphenol A polycarbonate matrix, and contains a polyimide structure with high rigidity, strength and modulus, which significantly improves the tensile strength, flexural strength and flexural modulus of the polycarbonate material.

[0015] During the heating and stirring process, the amino group of the amino polyimide-polycarbonate copolymer of the present invention can react with the carboxyl group and the epoxy group on the surface of the graphene oxide, thereby modifying the copolymer molecular chain on the graphene surface and reducing the agglomeration of the graphene. At the same time, the polyimide-polycarbonate copolymer has good compatibility with the bisphenol A polycarbonate matrix, thereby improving the compatibility between the graphene and the polycarbonate matrix, improving the dispersibility of the graphene, and making the graphene have a better reinforcement effect. Under the synergistic effect with the polyimide-polycarbonate copolymer, the mechanical properties of the polycarbonate material, such as the tensile strength, are significantly improved, and the uniformly dispersed graphene can further improve the thermal conductivity and thermal conductivity of the material. DETAILED DESCRIPTION

[0016] In order to more clearly illustrate the present invention and have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be understood as limiting the scope of the present invention. The raw materials and reagents used in the following examples can be obtained from conventional commercial channels or can be obtained by existing known methods unless otherwise specified.

[0017] Embodiment 1:

[0018] (1) Add 180 g of acetic anhydride, 144 g of pyridine, 20 g of bisphenol A type diether dianhydride, and 14 g of 3-amino-5-nitrobenzoic acid to a reaction vessel equipped with a condenser reflux tube, heat to 115° C., react for 18 h, filter, wash with water and ethanol in sequence, and add the product to 120 mL of thionyl chloride after drying, heat to 60° C., react for 3 h, remove thionyl chloride by vacuum distillation, and dry to obtain bisphenol A type nitrobenzoyl chloride monomer.

[0019] (2) Add 700 mL of N,N-dimethylformamide, 44 g of bisphenol A-type nitrobenzoyl chloride monomer, 50 g of polycarbonate diol (molecular weight 1000), and 12 g of triethylamine into a reaction container, heat to 45° C., stir and react for 24 hours, pour the solution into ethanol, filter, wash with water and ethanol in turn, and dry to obtain a nitropolyimide-polycarbonate copolymer.

[0020] (3) Add 2.5 kg of 37% concentrated hydrochloric acid and 340 g of iron powder to a reaction vessel equipped with a condenser reflux tube, heat to 65° C., stir, add 0.8 L of N,N-dimethylformamide solution containing 100 g of nitropolyimide-polycarbonate copolymer, and then heat to 110° C., react for 12 hours, add water, filter, wash the filter cake with water, sodium hydroxide solution, and water in turn, and dry to obtain aminopolyimide-polycarbonate copolymer.

[0021] (4) Add 1.2L N,N-dimethylformamide and 5g of graphene oxide into a reaction container, add 80g of amino polyimide-polycarbonate copolymer after ultrasonic dispersion, heat to 100°C, stir for 18h, remove N,N-dimethylformamide by vacuum distillation, and add the mixture and 1kg of polycarbonate into a twin-screw extruder after drying. The temperatures of zones 1 to 4 are 260°C, 270°C, 280°C, and 275°C, the head temperature is 260°C, the screw speed is 500r / min, and melt extrusion and granulation are performed to obtain a high-strength thermal conductive material for a mobile phone back cover.

[0022] Embodiment 2:

[0023] (1) Add 180 g of acetic anhydride, 126 g of pyridine, 20 g of bisphenol A type diether dianhydride, and 15.4 g of 3-amino-5-nitrobenzoic acid to a reaction vessel equipped with a condenser reflux tube, heat to 125° C., react for 12 h, filter, wash with water and ethanol in sequence, and add the product to 90 mL of thionyl chloride after drying, heat to 70° C., react for 4 h, remove thionyl chloride by vacuum distillation, and dry to obtain bisphenol A type nitrobenzoyl chloride monomer.

[0024] (2) Add 800 mL of N,N-dimethylformamide, 47 g of bisphenol A type nitrobenzoyl chloride monomer, 50 g of polycarbonate diol (molecular weight 1000), and 10 g of triethylamine into a reaction container, heat to 55° C., stir and react for 18 hours, pour the solution into ethanol, filter, wash with water and ethanol in turn, and dry to obtain a nitropolyimide-polycarbonate copolymer.

[0025] (3) Add 2 kg of 37% concentrated hydrochloric acid and 290 g of iron powder to a reaction vessel equipped with a condenser reflux tube, heat to 70° C., stir, add 0.8 L of N,N-dimethylformamide solution containing 100 g of nitropolyimide-polycarbonate copolymer, and then heat to 110° C., react for 18 hours, add water, filter, wash the filter cake with water, sodium hydroxide solution, and water in turn, and dry to obtain aminopolyimide-polycarbonate copolymer.

[0026] (4) Add 1.5L N,N-dimethylformamide and 10g of graphene oxide into a reaction container, add 150g of amino polyimide-polycarbonate copolymer after ultrasonic dispersion, heat to 100°C, stir for 24h, remove N,N-dimethylformamide by vacuum distillation, and add the mixture and 1kg of polycarbonate into a twin-screw extruder after drying. The temperatures of zones 1 to 4 are 260°C, 270°C, 280°C, and 275°C, the head temperature is 250°C, the screw speed is 400r / min, and melt extrusion and granulation are performed to obtain a high-strength thermal conductive material for a mobile phone back cover.

[0027] Embodiment 3:

[0028] (1) Add 800 mL of N,N-dimethylformamide, 46 g of bisphenol A-type nitrobenzoyl chloride monomer (prepared in Example 1), 50 g of polycarbonate diol (molecular weight 1000), and 10 g of triethylamine into a reaction container, heat to 40° C., stir and react for 24 hours, pour the solution into ethanol, filter, wash with water and ethanol in turn, and dry to obtain a nitropolyimide-polycarbonate copolymer.

[0029] (2) Add 3 kg of 37% concentrated hydrochloric acid and 440 g of iron powder to a reaction vessel equipped with a condenser reflux tube, heat to 65° C., stir, add 0.8 L of N,N-dimethylformamide solution containing 100 g of nitropolyimide-polycarbonate copolymer, then heat to 100° C., react for 18 hours, add water, filter, wash the filter cake with water, sodium hydroxide solution, and water in turn, and dry to obtain aminopolyimide-polycarbonate copolymer.

[0030] (3) Add 2L N,N-dimethylformamide and 30g of graphene oxide into a reaction container, add 200g of amino polyimide-polycarbonate copolymer after ultrasonic dispersion, heat to 120°C, stir for 12h, remove N,N-dimethylformamide by vacuum distillation, and add the mixture and 1kg of polycarbonate into a twin-screw extruder after drying. The temperatures of zones 1 to 4 are 260°C, 270°C, 280°C, and 275°C, the head temperature is 250°C, the screw speed is 500r / min, and melt extrusion and granulation are performed to obtain a high-strength thermal conductive material for mobile phone back cover.

[0031] Embodiment 4:

[0032] (1) Add 700 mL of N,N-dimethylformamide, 46 g of bisphenol A-type nitrobenzoyl chloride monomer (prepared in Example 1), 50 g of polycarbonate diol (molecular weight 1000), and 11 g of triethylamine into a reaction container, heat to 45° C., stir and react for 24 hours, pour the solution into ethanol, filter, wash with water and ethanol in turn, and dry to obtain a nitropolyimide-polycarbonate copolymer.

[0033] (2) Add 2.5 kg of 37% concentrated hydrochloric acid and 400 g of iron powder to a reaction vessel equipped with a condenser reflux tube, heat to 70° C., stir, add 1 L of N,N-dimethylformamide solution containing 100 g of nitropolyimide-polycarbonate copolymer, then heat to 100° C., react for 18 hours, add water, filter, wash the filter cake with water, sodium hydroxide solution, and water in turn, and dry to obtain aminopolyimide-polycarbonate copolymer.

[0034] (3) Add 2L N,N-dimethylformamide and 30g of graphene oxide to a reaction container, add 250g of amino polyimide-polycarbonate copolymer after ultrasonic dispersion, heat to 120°C, stir for 18h, remove N,N-dimethylformamide by vacuum distillation, and add the mixture and 1kg of polycarbonate to a twin-screw extruder after drying. The temperatures of zones 1 to 4 are 260°C, 270°C, 280°C, and 275°C, the head temperature is 250°C, the screw speed is 400r / min, and melt extrusion and granulation are performed to obtain a high-strength thermal conductive material for mobile phone back cover.

[0035] Comparative Example 1:

[0036] (1) 1 kg of polycarbonate was added into a twin-screw extruder, the temperatures of zones 1 to 4 were 260° C., 270° C., 280° C., and 275° C., the die temperature was 260° C., the screw speed was 500 r / min, and the polycarbonate was melt-extruded and granulated to obtain a high-strength thermal conductive material for a mobile phone back cover.

[0037] Comparative Example 2:

[0038] (1) 5 g of graphene oxide and 1 kg of polycarbonate were added to a twin-screw extruder, the temperatures of zones 1 to 4 were 260° C., 270° C., 280° C., and 275° C., the die temperature was 260° C., the screw speed was 500 r / min, and melt extrusion and granulation were performed to obtain a high-strength thermal conductive material for a mobile phone back cover.

[0039] Comparative Example 3:

[0040] (1) 80 g of amino polyimide-polycarbonate copolymer (prepared in Example 1) and 1 kg of polycarbonate were added to a twin-screw extruder. The temperatures of zones 1 to 4 were 260° C., 270° C., 280° C., and 275° C., the die temperature was 260° C., the screw speed was 500 r / min, and melt extrusion and granulation were performed to obtain a high-strength thermal conductive material for a mobile phone back cover.

[0041] Comparative Example 4:

[0042] (1) 1.2 L N, N-dimethylformamide and 5 g of graphene oxide were added to a reaction container, and 80 g of nitropolyimide-polycarbonate copolymer (prepared in Example 1) was added after ultrasonic dispersion. The mixture was heated to 100 ° C. and stirred for 18 h. N, N-dimethylformamide was removed by vacuum distillation. After drying, the mixture and 1 kg of polycarbonate were added to a twin-screw extruder. The temperatures of zones 1 to 4 were 260 ° C., 270 ° C., 280 ° C., and 275 ° C., the head temperature was 260 ° C., the screw speed was 500 r / min, and the mixture was melt-extruded and granulated to obtain a high-strength thermal conductive material for a mobile phone back cover.

[0043] Comparative Example 5:

[0044] (1) Add 180g of acetic anhydride, 144g of pyridine, 11.9g of 4,4'-biphenyl ether dianhydride, and 14g of 3-amino-5-nitrobenzoic acid to a reaction vessel equipped with a condenser reflux tube, heat to 115°C, react for 18h, filter, wash with water and ethanol in turn, and add the product to 120mL of thionyl chloride after drying, heat to 60°C, react for 3h, remove thionyl chloride by vacuum distillation, and dry to obtain nitrobenzoyl chloride monomer. The structural formula is:

[0045]

[0046] (2) Add 700 mL of N,N-dimethylformamide, 44 g of nitrobenzoyl chloride monomer, 50 g of polycarbonate diol (molecular weight 1000), and 12 g of triethylamine to a reaction container, heat to 45° C., stir and react for 24 hours, pour the solution into ethanol, filter, wash with water and ethanol in turn, and dry to obtain a nitropolyimide-polycarbonate copolymer.

[0047] (3) Add 2.5 kg of 37% concentrated hydrochloric acid and 340 g of iron powder to a reaction vessel equipped with a condenser reflux tube, heat to 65° C., stir, add 0.8 L of N,N-dimethylformamide solution containing 100 g of nitropolyimide-polycarbonate copolymer, and then heat to 110° C., react for 12 hours, add water, filter, wash the filter cake with water, sodium hydroxide solution, and water in turn, and dry to obtain aminopolyimide-polycarbonate copolymer.

[0048] (4) Add 1.2L N,N-dimethylformamide and 5g of graphene oxide into a reaction container, add 80g of amino polyimide-polycarbonate copolymer after ultrasonic dispersion, heat to 100°C, stir for 18h, remove N,N-dimethylformamide by vacuum distillation, and add the mixture and 1kg of polycarbonate into a twin-screw extruder after drying. The temperatures of zones 1 to 4 are 260°C, 270°C, 280°C, and 275°C, the head temperature is 260°C, the screw speed is 500r / min, and melt extrusion and granulation are performed to obtain a high-strength thermal conductive material for a mobile phone back cover.

[0049] Comparative Example 6

[0050] (1) Add 700 mL of N,N-dimethylformamide, 12.2 g of 5-nitrobenzoyl chloride, 50 g of polycarbonate diol (molecular weight 1000), and 12 g of triethylamine into a reaction container, heat to 45° C., stir and react for 24 hours, pour the solution into ethanol, filter, wash with water and ethanol in turn, and dry to obtain a nitropolycarbonate copolymer.

[0051] (2) Add 2.5 kg of 37% concentrated hydrochloric acid and 340 g of iron powder to a reaction vessel equipped with a condenser reflux tube, heat to 65° C., stir, add 0.8 L of N,N-dimethylformamide solution containing 100 g of nitropolyimide-polycarbonate copolymer, and then heat to 110° C., react for 12 h, add water, filter, wash the filter cake with water, sodium hydroxide solution, and water in turn, and dry to obtain an aminopolycarbonate copolymer.

[0052] (3) Add 1.2L N,N-dimethylformamide and 5g of graphene oxide into a reaction container, add 80g of amino polycarbonate copolymer after ultrasonic dispersion, heat to 100°C, stir for 18h, remove N,N-dimethylformamide by vacuum distillation, and add the mixture and 1kg of polycarbonate into a twin-screw extruder after drying. The temperatures of zones 1 to 4 are 260°C, 270°C, 280°C, and 275°C, the head temperature is 260°C, the screw speed is 500r / min, and melt extrusion and granulation are performed to obtain a high-strength thermal conductive material for mobile phone back cover.

[0053] The high-strength thermal conductive material is injected into a sample by an injection molding machine. The tensile properties are tested according to GB / T 1040.1-2018 standard. The bending properties are tested according to GB / T 9341-2000 standard.

[0054] The thermal conductivity was tested by a thermal conductivity tester using a steady-state method, and the sample was a circular sample with a radius of 6 cm.

[0055] Table 1 Performance test of high-strength thermal conductive materials

[0056]

[0057]

[0058] It can be seen from Table 1 that the polycarbonate material of Comparative Example 1 has low tensile properties and bending properties, and poor thermal conductivity and thermal conductivity.

[0059] Comparative Example 2 adds graphene oxide, which has poor compatibility with polycarbonate and poor dispersibility in the polycarbonate matrix, and has a low degree of improvement in the mechanical properties and thermal conductivity of the polycarbonate material.

[0060] Comparative Example 3 adds an amino polyimide-polycarbonate copolymer, which contains bisphenol A structural units and polycarbonate molecular chains, has good compatibility with the polycarbonate matrix, and contains a polyimide structure with high rigidity, strength and modulus, which significantly improves the mechanical strength of the polycarbonate material, and the tensile strength, flexural strength and flexural modulus are significantly higher than those of Comparative Example 1.

[0061] In Examples 1-4, amino polyimide-polycarbonate copolymers and graphene oxide are added. During the heating and stirring process, the amino groups of the polyimide-polycarbonate can react with the carboxyl groups and epoxy groups on the surface of the graphene oxide, thereby modifying the copolymer molecular chains to the graphene surface. Since the polyimide-polycarbonate copolymer has good compatibility with the polycarbonate matrix, the compatibility between the graphene and the polycarbonate matrix is ​​improved, the dispersibility of the graphene is improved, and the graphene has a better reinforcement effect. Under the synergistic effect with the polyimide-polycarbonate copolymer, the mechanical properties of the polycarbonate material, such as the tensile strength, are significantly improved, and the uniformly dispersed graphene can further improve the thermal conductivity and thermal conductivity of the material.

[0062] The nitropolyimide-polycarbonate copolymer added in Comparative Example 4 does not contain amino groups and cannot react with the surface of graphene oxide, and cannot improve the compatibility between graphene and the polycarbonate matrix. The dispersion of graphene is poor and the reinforcement effect is not good, resulting in mechanical properties such as tensile strength and thermal conductivity lower than those in the embodiments.

[0063] The amino polyimide-polycarbonate copolymer of Comparative Example 5 contains only polycarbonate molecular chains and does not contain bisphenol A structural units. Its compatibility with the polycarbonate matrix is ​​lower than that of the amino polyimide-polycarbonate copolymer of the embodiment, resulting in the polycarbonate material having lower mechanical properties such as tensile strength than the embodiment.

[0064] The amino polycarbonate copolymer of Comparative Example 6 does not contain a polyimide structure, and its reinforcing effect on polycarbonate is lower than that of the amino polyimide-polycarbonate copolymer of the embodiment, resulting in that the mechanical properties of the polycarbonate material, such as tensile strength, are lower than those of the embodiment.

[0065] The above describes some embodiments of the present invention, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.

Claims

1. A method for preparing a high-strength thermal conductive material for a mobile phone back cover, characterized in that: The preparation method is: Step S1, adding N,N-dimethylformamide, bisphenol A type nitrobenzoyl chloride monomer, polycarbonate diol, and triethylamine into a reaction container, stirring for reaction, pouring the solution into ethanol, filtering, washing, and drying to obtain a nitropolyimide-polycarbonate copolymer; Step S2, adding concentrated hydrochloric acid and iron powder to a reaction container equipped with a condenser reflux tube, heating to 65-70° C., adding N,N-dimethylformamide solution containing nitropolyimide-polycarbonate copolymer after stirring, and then heating to 100-110° C., reacting for 12-18 hours, adding water, filtering, washing the filter cake, and drying to obtain aminopolyimide-polycarbonate copolymer; Step S3, adding N,N-dimethylformamide and 0.5-3 parts by weight of graphene oxide into a reaction container, adding 8-25 parts by weight of amino polyimide-polycarbonate copolymer after ultrasonic dispersion, stirring and distilling under reduced pressure, adding the mixture and 100 parts by weight of polycarbonate into a twin-screw extruder after drying, melt-extruding and granulating to obtain a high-strength thermal conductive material for a mobile phone back cover.

2. The method for preparing the high-strength thermal conductive material for the mobile phone back cover according to claim 1, characterized in that: In the step S1, the masses of bisphenol A-type nitrobenzoyl chloride monomer and triethylamine are 88-94% and 20-24% of the mass of polycarbonate diol respectively.

3. The method for preparing the high-strength thermal conductive material for mobile phone back cover according to claim 1, characterized in that: The reaction in step S1 is carried out at 40-55° C. for 18-24 h.

4. The method for preparing the high-strength thermal conductive material for the mobile phone back cover according to claim 1, characterized in that: In step S2, the masses of concentrated hydrochloric acid and iron powder are 2000-3000% and 290-440% of the mass of the nitropolyimide-polycarbonate copolymer respectively, and the mass fraction of concentrated hydrochloric acid is 36-38%.

5. The method for preparing the high-strength thermal conductive material for mobile phone back cover according to claim 1, characterized in that: The stirring temperature in step S3 is 100-120° C. and the stirring time is 12-24 hours.

6. The method for preparing the high-strength thermal conductive material for the mobile phone back cover according to claim 1, characterized in that: In step S3, the temperature of zones 1 to 4 of the twin-screw extruder is 260-275° C., the die temperature is 250-260° C., and the screw speed is 400-500 r / min.

7. The method for preparing the high-strength thermal conductive material for the mobile phone back cover according to claim 2, characterized in that: The preparation method of the bisphenol A type nitrobenzoyl chloride monomer is as follows: acetic anhydride, pyridine, bisphenol A type diether dianhydride, and 3-amino-5-nitrobenzoic acid are added to a reaction container equipped with a condenser reflux tube, heated to 115-125° C., reacted for 12-18 hours, filtered and washed, and after drying, the product is added to thionyl chloride, heated to 60-70° C., reacted for 3-4 hours, distilled under reduced pressure, and dried to obtain the bisphenol A type nitrobenzoyl chloride monomer.

8. The method for preparing the high-strength thermal conductive material for the mobile phone back cover according to claim 7, characterized in that: The mass of the pyridine is 70-80% of the mass of the acetic anhydride.

9. The method for preparing the high-strength thermal conductive material for mobile phone back cover according to claim 7, characterized in that: The mass of the 3-amino-5-nitrobenzoic acid is 70-77% of the mass of bisphenol A diether dianhydride.

Citation Information

Patent Citations

  • A method for preparing a graphene / polycarbonate composite material

    CN112094491B